Health risk assessment of heavy metals and metalloids via dietary intake of a potential vegetable (Coriandrum sativum L.) grown in contaminated water irrigated agricultural sites of Sargodha, Pakistan. Issue 3 (2nd April 2016) - Ahmad, Kafeel; Ashfaq, Asma; Khan, Zafar Iqbal; Ashraf, Muhammad; Akram, Nudrat Aisha; Yasmin, Sumaira; Batool, Aima Iram; Sher, Muhammad; Shad, Hazoor Ahmad; Khan, Ameer; Rehman, Saif Ur; Ullah, Muhammad Fahad; et al.
ABSTRACT: Levels of Mo, As, Se, Fe, Cu, Zn, Ni, and Pb were determined in a vegetable commonly consumed in Pakistan. Samples were collected from three different sites (Ratokala, Phularwan, and Mailowal) supplied with three different water sources. Mo and Pb in water and Mo and As in C. sativum were higher than the suggested standards at the international level. Lower bioconcentration factor and pollution load index were seen at Site-I than at other sites. A positive association was found between the rhizosphere metals and those of the vegetable at all three sites. Enrichment factor at three sites ranged from 0.28 to 10.39. The highest value of daily intake of metals was found for Fe (0.245 mg/kg/day) and of the health risk index for As (70.41) at the wastewater inundated site. It is inferred that uptake of Mo, As, Cu, Ni, and Pb through C . sativum represents a high health danger to the individuals using this vegetable.